Cover Image, Volume 61, Issue 8. Issue 8 (7th July 2022) - Srivastava, Ritesh K.; Guroji, Purushotham; Jin, Lin; Mukhtar, M. Shahid; Athar, Mohammad
Abstract : The cover image is based on the Research Article Combined inhibition of BET bromodomain and mTORC1/2 provides therapeutic advantage for rhabdomyosarcoma by switching cell death mechanism by Ritesh K. Srivastava et al., https://doi.org/10.1002/mc.23414 .